lectures.alex.balgavy.eu

Lecture notes from university.
git clone git://git.alex.balgavy.eu/lectures.alex.balgavy.eu.git
Log | Files | Refs | Submodules

index.md (4275B)


      1 +++
      2 title = 'Proof systems and derivation'
      3 +++
      4 # Proof systems and derivation
      5 ## Proof systems
      6 Hilbert systems:
      7 - proof is sequence of numbered formulas
      8 - every formula is: an axiom, or result of applying a derivation rule
      9 
     10 Sufficient to have 2 axioms and a rule:
     11 - K: φ → ψ → φ
     12 - S: (φ → ψ → θ) → (φ → ψ) → (φ → θ)
     13 - modus ponens: if φ and (φ → ψ), then ψ
     14 
     15 Rules will be given, don't need to be memorized.
     16 
     17 Admissible rule:
     18 
     19 ![Admissible rule definition](admissible-rule.png)
     20 
     21 Proof system K is sound and complete with respect to all frames, ⊢K φ iff ⊨ φ.
     22 
     23 Soundness and completeness results (**note:** the frame classes _need_ to be memorized)
     24 - K sound and complete for all frames
     25 - T sound and complete for all _reflexive_ frames
     26     - T: K with □ p → p
     27 - S4 sound and complete for all _reflexive-transitive_ frames
     28     - S4: T with □ p → □ □ p
     29 - S5 sound and complete for all frames with R an equivalence relation
     30     - S5: S4 with ¬ □ p → □ ¬ □ p
     31 
     32 ## Example of derivation
     33 Give derivation in K of ◇ φ ∧ □ (φ → ψ) → ◇ ψ.
     34 Same as example in book <abbr title='Modal Logic for Open Minds (Benthem)'>MLOM</abbr> page 52.
     35 
     36 First, work backwards from the goal towards an axiom or tautology:
     37 
     38 <pre>
     39 ◇ φ ∧ □ (φ → ψ) → ◇ ψ ≡ □ (φ → ψ) → (◇ φ → ◇ ψ)                 [you can rewrite a conjunction as an implication]
     40                       ≡ □ (φ → ψ) → (¬ □ ¬ φ → ¬ □ ¬ ψ)         [rewrite diamond to ¬ □ ¬]
     41                       ≡ □ (φ → ψ) → (□ ¬ ψ → □ ¬ φ)             [rewrite contrapositive (¬ a → ¬ b) to (b → a)]
     42                       ≡ □ (φ → ψ) → □ (¬ ψ → ¬ φ)               [box distribution over implication]
     43                       ≡ □ (φ → ψ) → □ (φ → ψ)                   [again contrapositive]
     44                       ≡ (φ → ψ) → (φ → ψ)                       [because if derivable (a → b), then derivable (□ a → □ b)]
     45 </pre>
     46 
     47 We arrive at a tautology.
     48 
     49 Then you write it out in a Hilbert-style proof, starting with the tautology/axiom.
     50 PROP means rewriting in propositional logic.
     51 
     52 1. (φ → ψ) → (¬ ψ → ¬ φ). PROP.
     53 2. □ (φ → ψ) → □ (¬ ψ → ¬ φ). DISTR, 1.
     54 3. □ (p → q) → □ p → □ q. modal distribution (i.e., this is an axiom in K that we use)
     55 4. □ (¬ ψ → ¬ φ) → □ ¬ ψ → □ ¬ φ. substitution, 3 (i.e., substitute stuff in the axiom).
     56 5. □ (φ → ψ) → □ ¬ ψ → □ ¬ φ. PROP, 2, 4.
     57 6. □ (φ → ψ) → ¬ ◇ ψ → ¬ ◇ φ. definition of ◇, □.
     58 7. □ (φ → ψ) → ◇ φ → ◇ ψ. PROP, 6.
     59 8. ◇ φ ∧ □ (φ → ψ) → ◇ ψ. PROP, 7.
     60 
     61 <details>
     62 <summary>Why you can rewrite a conjunction as an implication</summary>
     63 
     64 You can safely rewrite a conjunction to an implication: (a ∧ b → c) ≡ a → (b → c).
     65 Remember that implication is right-associative!
     66 
     67 If you don't trust me, I didn't trust myself either so I made a truth table:
     68 
     69 <table>
     70 <thead>
     71 <tr>
     72 <th>a</th>
     73 <th>b</th>
     74 <th>c</th>
     75 <th>b → c</th>
     76 <th>a ∧ b</th>
     77 <th>a → c</th>
     78 <th>a ∧ b → c</th>
     79 <th>b → (a → c)</th>
     80 <th>a → (b → c)</th>
     81 </tr>
     82 </thead>
     83 <tbody>
     84 <tr>
     85 <td>0</td>
     86 <td>0</td>
     87 <td>0</td>
     88 <td>1</td>
     89 <td>0</td>
     90 <td>1</td>
     91 <td>1</td>
     92 <td>1</td>
     93 <td>1</td>
     94 </tr>
     95 
     96 <tr>
     97 <td>0</td>
     98 <td>0</td>
     99 <td>1</td>
    100 <td>1</td>
    101 <td>0</td>
    102 <td>1</td>
    103 <td>1</td>
    104 <td>1</td>
    105 <td>1</td>
    106 </tr>
    107 
    108 <tr>
    109 <td>0</td>
    110 <td>1</td>
    111 <td>0</td>
    112 <td>0</td>
    113 <td>0</td>
    114 <td>1</td>
    115 <td>1</td>
    116 <td>1</td>
    117 <td>1</td>
    118 </tr>
    119 
    120 <tr>
    121 <td>0</td>
    122 <td>1</td>
    123 <td>1</td>
    124 <td>1</td>
    125 <td>0</td>
    126 <td>1</td>
    127 <td>1</td>
    128 <td>1</td>
    129 <td>1</td>
    130 </tr>
    131 
    132 <tr>
    133 <td>1</td>
    134 <td>0</td>
    135 <td>0</td>
    136 <td>1</td>
    137 <td>0</td>
    138 <td>0</td>
    139 <td>1</td>
    140 <td>1</td>
    141 <td>1</td>
    142 </tr>
    143 
    144 <tr>
    145 <td>1</td>
    146 <td>0</td>
    147 <td>1</td>
    148 <td>1</td>
    149 <td>0</td>
    150 <td>1</td>
    151 <td>1</td>
    152 <td>1</td>
    153 <td>1</td>
    154 </tr>
    155 
    156 <tr>
    157 <td>1</td>
    158 <td>1</td>
    159 <td>0</td>
    160 <td>0</td>
    161 <td>1</td>
    162 <td>0</td>
    163 <td>0</td>
    164 <td>0</td>
    165 <td>0</td>
    166 </tr>
    167 
    168 <tr>
    169 <td>1</td>
    170 <td>1</td>
    171 <td>1</td>
    172 <td>1</td>
    173 <td>1</td>
    174 <td>1</td>
    175 <td>1</td>
    176 <td>1</td>
    177 <td>1</td>
    178 </tr>
    179 </tbody>
    180 </table>
    181 
    182 You see that the right three columns all have the same values, so semantically the formulas are the same.
    183 
    184 </details>
    185